2018
DOI: 10.3892/ol.2018.8699
|View full text |Cite
|
Sign up to set email alerts
|

PCDHGA12 methylation biomarker in bronchial washing specimens as an adjunctive diagnostic tool to bronchoscopy in lung cancer

Abstract: The use of bronchoscopy is central to the diagnosis of lung cancer. However, the sensitivity of bronchoscopy is low. In addition, bronchial washing cytology, which is a routine adjunctive test, does not significantly improve the performance of bronchoscopy owing to its low sensitivity. To enhance the diagnostic performance of bronchoscopy, the protocadherin GA12 () methylation biomarker in bronchial washings was introduced as a novel adjunctive diagnostic test. A total of 98 patients who underwent bronchoscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 32 publications
1
15
1
Order By: Relevance
“…Methylated SHOX2 and RASSF1A gene promoters were detected in lavage fluid from 322 patients with a sensitivity of 81% for lung cancer detection (Zhang et al, 2017). Other studies have also revealed high sensitivity for lung cancer detection using bronchoalveolar lavage fluid, with 75% and 78% for PCDHGA12 (Jeong et al, 2018) and SHOX2 (Dietrich et al, 2012) methylated DNA, respectively. However, these studies use different methodologies to process the lavage samples, so cannot be directly compared.…”
Section: Designing An Effective Assaymentioning
confidence: 96%
“…Methylated SHOX2 and RASSF1A gene promoters were detected in lavage fluid from 322 patients with a sensitivity of 81% for lung cancer detection (Zhang et al, 2017). Other studies have also revealed high sensitivity for lung cancer detection using bronchoalveolar lavage fluid, with 75% and 78% for PCDHGA12 (Jeong et al, 2018) and SHOX2 (Dietrich et al, 2012) methylated DNA, respectively. However, these studies use different methodologies to process the lavage samples, so cannot be directly compared.…”
Section: Designing An Effective Assaymentioning
confidence: 96%
“…In our study, the sensitivity of the panel in bronchial washing and brushing specimens was 74.8% and 86.5%, respectively, with specificity at 96.4% and 96.7%, respectively, which was higher than other methylation studies that used similar bronchial materials ranging from 74% to 95%. 10,25,29,30,39 While the sensitivity and specificity of brushing and washing are not higher than those achieved with bronchoscopy procedures incorporating cytology, ROSE technology and tissue histology, the NPV of the combination of bronchoscopy with q-MSP panel increases by 5.2% and 6.5% in bronchial washing and brushing sample groups, respectively. This increase may prevent further invasive procedures in some patients.…”
Section: Discussionmentioning
confidence: 98%
“…There have been few studies reported on the use of bronchoscopic brushing samples for diagnosing lung cancer 30,38,39 . However, the limited sample size or unsatisfactory performance of biomarkers in these studies make it difficult to draw definitive conclusions about the usefulness of brushing samples in diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations